Certain specifics of the metaphorical representation of the concept "success" in American linguistic culture - Zharkynbekova , Sh. K.; Zadanova E. В (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The objective of the article is to analyze the metaphorical representation of the concept «success» in American linguistic culture. The material for the analysis is aphorisms, quotes, books on success in English. The study is based on the analysis of statements, in which the lexical unit «success», as well as its synonymic variants are considered as part of the metaphorical expression. For American society «success» is one of the most important components of culture, so it is interesting to observe what place in the everyday consciousness of the American takes the advancement to success and how success is conceptualized by means of language. Consideration of the metaphorical content of the concept of «success» in different languages allows us to take a deeper look at its content and to describe the national and cultural peculiarities. The methodology for studying cultural dominants is in the form of sampling lexical, paremic, phraseological units, sayings and quotations from success literature, blogs, and the electronic Corpus of Contemporary American English. The results of the study showed that the concept «success» metaphorically acts as an object, is likened to a living being, has a moving intentionality, is verbalized by a variety of metaphors, including ontological. The basic projections of the concept «success» were revealed. The frequency of projecting success through failure is several times higher than the number of other projections. This indicates that for the ordinary consciousness of the American, failure is one of the essential markers of success.